Police Technology: An Investigation into the Benefits for Law Enforcement - Shuping, Jason (2018)
The police must perform their duties every hour of each day during the year. While they have been able to complete their responsibilities in the past, they have become more efficient due to technological advancements. Such technological advancements as fingerprinting, the 911 system, or vehicle location systems have revolutionized policing in the modern era. Other forms of technology have been a benefit to police as this paper will prove